The screening of probiotic lactic acid bacteria from honey of stingless bee from West Sumatra, Indonesia and using as starter culture (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Melia S, Aritonang SN, Juliyarsi I, Kurnia YF, Rusdimansyah, Hernita VO. 2022. The screening of probiotic lactic acid bacteria from honey of stingless bee from West Sumatra, Indonesia and using as starter culture. Biodiversitas 23: 6379-6385. This study aimed to isolate probiotic lactic acid bacteria (LAB) from stingless bee honey (Galo-galo) and apply it as a starter culture. This research used stingless bee honey (Galo-galo) from west Sumatra, Indonesia. There are 6 types of honey bees, namely Tetragonula sarawakensis (TS), Tetragonula testaceitarsis (TT), Tetragonula minangkabau (MK), Tetrigona binghami (TB), Geniotrigona thoracica (TR) and Heterotrigona itama (IT). The screening of probiotics was evaluated as the LAB isolates' ability to resist acid (pH 3), bile salts (0xgall 0.5%), and antimicrobial activity against pathogenic bacteria. Based on the probiotic selection, the TB1 isolate from Tetrigona binghami honey had an acid tolerance of 82.75%, bile salt tolerance of 94.44%, and the highest antimicrobial activity against pathogenic bacteria with more excellent resistance than antibiotics. The identification with 16S rRNA showed that the TB1 bacterial isolate had 100% similarity with Lactobacillus plantarum SN13TFurthermore, starter culture inoculated with 6% L.plantarum SN13T met the starter culture parameters, with a pH of 4.7, titratable acidity of 1.46%, and lactic acid bacteria counts of 9.0 x 109 CFU/mL. L.plantarum SN13T is a candidate probiotic bacteria isolated from the stingless bee honey (Tetrigona binghami). This bacteria has the potential to be developed as a starter for fermented milk processing in the food industry.
Keywords: Fermented milk, Galo-galo, Lactobacillus plantarum SN13T, probiotic, stingless bee